I once was lost : my search for God in America - Lemon, Don, 1966- (Little, Brown and Company, 2024)
Journalist Don Lemon always had a complicated relationship with God. He cherished the Southern Black church he was raised in, but struggled with the fundamentalist rejection of his right to exist as a gay man--one who wanted to marry his longtime love in a church wedding. In his work as a reporter, he saw Americans losing faith in a higher power, in institutions, and in each other. Setting out to understand the place that religion has in our lives today, Don connected with ancient stories, sparking memories, conversations, and chance encounters. Then, suddenly, his world unraveled: Don was ousted from his high-profile network news job and tasked with redefining his role in the shifting media landscape. But through a year of personal changes and professional whiplash, he ultimately found what he was seeking: grace. "I once was lost" is a prayer for a country that reflects the multifaceted image of God, and a call to those who believe in humanity to fight for it